Parama bismaẏa Bālaka Ṭhākura : janmasiddha Ṭhākura Śrīśrībāllaka Brahmacārī Mahārājera tattvamaẏa jībanera kaẏekaṭi kāhinī - Rāẏadā (Āra. Ena. Āra. Pābaliśārsa ; prāptisthāna Bālaka Brahmacārī Dhāma, 1981)
Early life Bālaka Brahmacārī, b. 1920, Hindu religious leader.